Impact Analysis of High-speed Rail Investment on Regional Economic Inequality: A Hybrid Approach Using a Transportation Network-CGE Model. (1st July 2019) - Kim, Euijune; Yi, Yoojin
This paper analyses the impact of the establishment of a high-speed rail (HSR) link between less and more developed regions on regional economic inequality in South Korea. We applied a hybrid method composed of a transportation network analysis and a multi-regional Computable General Equilibrium (CGE) model. Results indicate that a new HSR link from a less developed region to the capital region with a pre-developed HSR line leads to regional divergence in terms of the regional production growth rate. However, the regional disparity could decrease due to an increase in interregional mobility of labour and capital.